Electric Field Waveforms of Very Close Negative Cloud to Ground Flashes - Shamsul Ammar Shamsul Baharin, Mohd Riduan Ahmad (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
Negative cloud-to-ground brings down negative charge from cloud to ground. In this paper, observations of the characteristics of fast and slow electric field within reversal distance (less than 7-8 km from lightning sensor) are reported. A total of four negative cloud to ground lashes detected very close to our measurement site in Universiti Teknikal Malaysia Melaka on 12th November 2019 were selected for analysis. The captured waveforms are compared with the location data provided by Tenaga Nasional Berhad Research (TNBR) for validation purposes. It can be observed that electric field changes of stepped leader and return stroke are always positive whether beyond or within reversal distance. Meanwhile, for cloud activities, the electric field change is always negative within reversal distance.